Living Ring-Opening Polymerization of O-Carboxyanhydrides: The Search for Catalysts - Zhong, Yongliang; Tong, Rong (Frontiers in Chemistry, 2018)
Biodegradable poly(α-hydroxy acids) can be synthesized by means of ring-opening polymerization (ROP) of O-carboxyanhydrides (OCAs). Numerous catalysts have been developed to control the living polymerization of OCAs. Here we review the rationale for the use of OCA, the desirable features for and important attributes of catalysts for the ROP of OCAs, and specific examples that have been developed.